Optical film, method for producing optical film, optical member, and image display device
The optical film with a resin film and easy-to-adhesive layer, featuring specific amino groups and a binder resin, addresses adhesion and durability issues by stabilizing alkaline components, resulting in improved adhesion and blocking resistance.
Patent Information
- Application Number
- JP2023525880
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-31
- Filing Date
- 2022-05-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-05-31
AI Technical Summary
Existing optical films face challenges in achieving optimal adhesion between the film and adhesive layers, with difficulties in controlling the amount of alkaline components in the adhesive layer, leading to inconsistent adhesion and durability issues.
The development of an optical film with a resin film and an easy-to-adhesive layer containing a polymer with amino groups, specifically including 2nd and 3rd grade amino groups, and a binder resin, which promotes uniform dispersion of fine particles and stabilizes alkaline components, enhancing adhesion and blocking resistance.
The solution results in an optical film with improved adhesion, controlled alkaline component content, and enhanced blocking resistance, ensuring consistent performance under varying environmental conditions.
Smart Images

Figure 0007623482000001 
Figure 0007623482000002 
Figure 0007623482000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical film, a method for producing an optical film, an optical member, and an image display device. [Background technology]
[0002] Liquid crystal display devices and organic EL display devices are used for various image displays such as monitors and televisions. Liquid crystal display devices use polarizing plates. Organic EL display devices use polarizing plates and 1 / 4 wavelength plates to prevent reflection of external light. Polarizing plates usually include a polarizer and a polarizer protective film attached to at least one surface of the polarizer via an adhesive layer.
[0003] Conventionally, cellulose-based films have been widely used as polarizer protective films. In recent years, films made of acrylic, polyester, polycarbonate, cyclic polyolefin, etc. have also been used. Although these films have low moisture permeability and excellent durability compared to cellulose-based films, the adhesion between these films and PVA-based polarizers is inferior to that of cellulose-based films. For this reason, a method has been proposed in which an easy-adhesion layer is provided on the surface of these films to improve the adhesion between the film and the polarizer. For example, Patent Document 1 describes that by providing an easy-adhesion layer containing fine particles and a binder resin on the surface of an acrylic film, it is possible to not only improve the adhesion between the acrylic film and the polarizer but also suppress blocking.
[0004] Patent Document 2 describes that an alkaline component such as ammonia or amine is contained in the easy-adhesion layer, that the alkaline component remaining in excess in the easy-adhesion layer deteriorates the polarizer, but that the alkaline component can also act as a catalyst for promoting the reaction of the binder resin (precursor), and that the alkaline component improves the dispersibility of inorganic fine particles present in the easy-adhesion layer. It also describes that the alkaline component can be volatilized and removed by heating the easy-adhesion composition applied to a film substrate, thereby reducing the amount of alkaline component remaining in the easy-adhesion layer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-55062 A [Patent Document 2] JP 2020-16872 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, for example, the adhesion between the film and the easy-adhesion layer and the uniformity of the easy-adhesion layer have not been fully considered. Also, for example, in the technique described in Patent Document 2, it is relatively difficult to adjust the amount of the remaining alkali component. [Means for solving the problem]
[0007] In view of the above circumstances, the present inventors conducted extensive research and completed the inventions described below in [1] to [9]. [1] An optical film having a resin film and an easy-adhesion layer formed on a surface of the resin film, the easy-adhesion layer containing a binder resin, a polyamine, and fine particles, the polyamine being a polymer having a plurality of amino groups, the plurality of amino groups including at least one selected from the group consisting of a secondary amino group and a tertiary amino group, and the content of the polyamine in the easy-adhesion layer being 0.0090% by weight to 1.4100% by weight. [2] The optical film according to [1], wherein the binder resin comprises a urethane resin. [3] The optical film according to [1] or [2], wherein the plurality of amino groups include a primary amino group, the secondary amino group, and the tertiary amino group. [4] The optical film described in any one of claims [1] to [3], wherein the polyamine comprises a polyalkyleneimine. [5] The optical film according to [4], wherein the polyalkyleneimine contains a primary amino group, the secondary amino group, and the tertiary amino group, and has a branched structure. [6] The optical film described in any one of claims [1] to [5], wherein the resin film contains a (meth)acrylic polymer. [7] An optical member comprising the optical film according to any one of [1] to [6]. [8] An image display device comprising the optical film according to any one of [1] to [6]. [9] A method for producing an optical film according to any one of [1] to [6], comprising the steps of: applying an easy-adhesion composition containing a binder resin, a polyamine, and fine particles onto a surface of a resin film to form a coating film of the easy-adhesion composition; and drying the coating film to form an easy-adhesion layer containing the binder resin, the polyamine, and the fine particles on the surface of the resin film, wherein the polyamine is a polymer having a plurality of amino groups, and the plurality of amino groups include at least one selected from the group consisting of a secondary amino group and a tertiary amino group. Effect of the Invention
[0008] The optical film of the present invention has a resin film and an easy-adhesion layer, and has excellent adhesion between them. In addition, the optical film of the present invention has an alkali component contained in the easy-adhesion layer, which is a polymer that is not easily volatilized during the production of the optical film, so that the amount of the alkali component contained in the easy-adhesion layer is easily controlled. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Unless otherwise specified, the term "resin" in this specification is a broader concept than "polymer." A resin may be composed of, for example, one or more polymers, and may contain materials other than polymers, such as additives such as ultraviolet absorbers, antioxidants, and fillers, compatibilizers, and stabilizers, as necessary.
[0010] [Optical film] The optical film according to this embodiment has a resin film and an easy-adhesion layer formed on the surface of the resin film.
[0011] [Resin film] The resin film is not particularly limited, but may be a film made of a material such as a (meth)acrylic polymer, polyester, polycarbonate, or cyclic polyolefin. Among these, an acrylic resin film obtained by molding an acrylic resin containing a (meth)acrylic polymer is preferable. The content of the (meth)acrylic polymer in the acrylic resin is usually 30% by weight or more, preferably 50% by weight or more, more preferably 70% by weight or more, particularly preferably 90% by weight or more, and most preferably 95% by weight or more.
[0012] The (meth)acrylic polymer is a polymer having a structural unit ((meth)acrylic acid ester unit) derived from a (meth)acrylic acid ester monomer. The content of the (meth)acrylic acid ester unit in the (meth)acrylic polymer is usually 10% by weight or more, preferably 30% by weight or more, more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The weight average molecular weight of the (meth)acrylic polymer is preferably 10,000 to 500,000, and more preferably 50,000 to 300,000.
[0013] The (meth)acrylic acid ester unit is, for example, a structural unit derived from each monomer of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, and 2,3,4,5-tetrahydroxypentyl (meth)acrylate. The (meth)acrylic polymer preferably has a structural unit derived from methyl (meth)acrylate, and in this case, the optical properties and thermal stability of the finally obtained optical film are improved. The (meth)acrylic polymer may have two or more kinds of (meth)acrylic acid ester units.
[0014] The (meth)acrylic polymer may have a structural unit other than the (meth)acrylic acid ester unit. Such a structural unit is, for example, a structural unit derived from each monomer of styrene, vinyl toluene, α-methylstyrene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, acrylonitrile, methacrylonitrile, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinylpyrrolidone, and N-vinylcarbazole. The (meth)acrylic polymer may have two or more of these structural units. When the (meth)acrylic polymer has an N-vinylpyrrolidone unit or an N-vinylcarbazole unit, the degree of freedom in controlling the wavelength dispersion of birefringence in the optical film is improved. For example, a retardation film showing wavelength dispersion (so-called reverse wavelength dispersion) in which the birefringence becomes smaller (the absolute value of the retardation becomes smaller) as the wavelength of light becomes shorter in the visible light range can be obtained. The retardation film is suitable as a positive retardation film.
[0015] The (meth)acrylic polymer may have a ring structure in the main chain. Such a (meth)acrylic polymer can be obtained, for example, by copolymerizing a (meth)acrylic acid ester monomer with a monomer having a ring structure, or by polymerizing a monomer group containing a (meth)acrylic acid ester monomer and then carrying out a cyclization reaction. When the (meth)acrylic polymer has a ring structure in the main chain, the total content of the (meth)acrylic acid ester unit and the ring structure may be 50% by weight or more.
[0016] In addition, when a ring structure is introduced into the main chain by a cyclization reaction after polymerization, the (meth)acrylic polymer is preferably formed by copolymerization of a monomer group including a monomer having a hydroxyl group and / or a carboxylic acid group. Examples of the monomer having a hydroxyl group include methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, butyl 2-(hydroxymethyl)acrylate, methyl 2-(hydroxyethyl)acrylate, methallyl alcohol, and allyl alcohol. Examples of the monomer having a carboxylic acid group include acrylic acid, methacrylic acid, crotonic acid, 2-(hydroxymethyl)acrylic acid, and 2-(hydroxyethyl)acrylic acid. Two or more of these monomers may be used. It is not necessary that all of the monomers are converted into a ring structure during the cyclization reaction, and the (meth)acrylic polymer after the cyclization reaction may have a structural unit derived from these monomers.
[0017] The (meth)acrylic polymer preferably has a ring structure in the main chain. In this way, the acrylic resin film has excellent heat resistance and hardness. In addition, when it is made into a stretched film, it exhibits a large retardation, so it is suitable for use as a retardation film or a polarizer protective film having the function of a retardation film.
[0018] The ring structure is, for example, at least one selected from an N-substituted maleimide structure, a maleic anhydride structure, a glutarimide structure, a glutaric anhydride structure, and a lactone ring structure. The N-substituted maleimide structure is, for example, a cyclohexylmaleimide structure, a methylmaleimide structure, a phenylmaleimide structure, and a benzylmaleimide structure. From the viewpoint of the heat resistance of the optical film, the ring structure is preferably a lactone ring structure, a cyclic imide structure (for example, an N-alkyl-substituted maleimide structure, a glutarimide structure), or a cyclic anhydride structure (for example, a maleic anhydride structure and a glutaric anhydride structure). The optical film of the present embodiment can be used as a retardation film. From the viewpoint of imparting a positive retardation to the optical film as a retardation film, the ring structure is preferably a lactone ring structure, a glutarimide structure, and a glutaric anhydride structure. From the viewpoint of improving the wavelength dispersion of birefringence in the retardation film, the ring structure is preferably a lactone ring structure.
[0019] The glutaric anhydride structure and the glutarimide structure are shown in the following general formula (1).
[0020] [ka]
[0021] R in the general formula (1) 1 , R 2 are each independently a hydrogen atom or a methyl group, and X 1 is an oxygen atom or a nitrogen atom. X 1 is an oxygen atom, R 3 does not exist, and X 1 is a nitrogen atom, R 3 is a hydrogen atom, a linear alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group, or a phenyl group.
[0022] X 1When X is an oxygen atom, the ring structure represented by the general formula (1) is a glutaric anhydride structure. The glutaric anhydride structure can be formed, for example, by intramolecular dealcoholization cyclocondensation of a copolymer of a (meth)acrylic acid ester and (meth)acrylic acid. 1 When is a nitrogen atom, the ring structure represented by the general formula (1) is a glutarimide structure. The glutarimide structure can be formed, for example, by imidizing a (meth)acrylic acid ester polymer with an imidizing agent such as methylamine.
[0023] The maleic anhydride structure and the N-substituted maleimide structure are shown in the following general formula (2).
[0024] [ka]
[0025] R in the general formula (2) 4 , R 5 are each independently a hydrogen atom or a methyl group, and X 2 is an oxygen atom or a nitrogen atom. X 2 is an oxygen atom, R 6 does not exist, and X 2 is a nitrogen atom, R 6 is a hydrogen atom, a linear alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group, or a phenyl group.
[0026] X 2 When X is an oxygen atom, the ring structure represented by the general formula (2) is a maleic anhydride structure. The maleic anhydride structure can be formed, for example, by copolymerizing maleic anhydride with a (meth)acrylic acid ester. 2 When is a nitrogen atom, the ring structure represented by general formula (2) is an N-substituted maleimide structure.
[0027] In the methods for forming the ring structures exemplified in the description of general formulas (1) and (2), all of the polymers used for forming the respective ring structures have (meth)acrylic acid ester units as constituent units, and therefore the resulting resin is an acrylic resin.
[0028] The lactone ring structure is shown in the following general formula (3).
[0029] [ka]
[0030] In the general formula (3), R 7 , R 8 and R 9 are each independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms. The organic residue may contain an oxygen atom.
[0031] The organic residue in general formula (3) is, for example, an alkyl group having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, or a propyl group; an unsaturated aliphatic hydrocarbon group having 2 to 20 carbon atoms, such as an ethenyl group or a propenyl group; or an aromatic hydrocarbon group having 6 to 20 carbon atoms, such as a phenyl group or a naphthyl group. One or more hydrogen atoms in the alkyl group, the unsaturated aliphatic hydrocarbon group, or the aromatic hydrocarbon group may be substituted with at least one type of group selected from a hydroxyl group, a carboxyl group, an ether group, and an ester group.
[0032] Although the general formula (3) shows a 6-membered lactone ring structure, the lactone ring structure is not limited thereto. For example, it may be a 4- to 8-membered ring. In view of excellent stability of the ring structure, a 5- or 6-membered ring is preferred, and a 6-membered ring is more preferred.
[0033] When the (meth)acrylic polymer has a ring structure in the main chain, the content of the ring structure in the polymer is not particularly limited, but is usually 5 to 90% by weight, preferably 10 to 70% by weight, more preferably 10 to 60% by weight, and even more preferably 10 to 50% by weight. When the content of the ring structure is high (for example, 10% by weight or more), the heat resistance, solvent resistance, and surface hardness of the film are particularly excellent. When the content of the ring structure is low (for example, 70% by weight or less), the acrylic resin film is particularly excellent in terms of ease of stretching and handling during production.
[0034] When the ring structure of the main chain is other than a lactone ring structure (for example, an N-substituted maleimide structure, a maleic anhydride structure, a glutarimide structure, or a glutaric anhydride structure), the content of the ring structure is not particularly limited, and is, for example, 5 to 90 mass %, preferably 10 to 70 mass %, more preferably 10 to 60 mass %, and further preferably 10 to 50 mass %.
[0035] When the ring structure of the main chain is a lactone ring structure, the content of the ring structure is not particularly limited, but is, for example, 5 to 90 mass%, preferably 10 to 80 mass%, more preferably 10 to 70 mass%, and even more preferably 10 to 60 mass%.
[0036] The (meth)acrylic polymer having a ring structure in the main chain can be formed by a known method. The (meth)acrylic polymer having a lactone ring structure in the main chain is, for example, a polymer described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084, and can be formed by the method described in the publications.
[0037] The (meth)acrylic polymer having a glutaric anhydride structure in the main chain is, for example, a polymer described in JP-A Nos. 2006-283013, 2006-335902, and 2006-274118, and can be formed by the method described in these publications.
[0038] (Meth)acrylic polymers having a glutarimide structure in the main chain are polymers described in, for example, JP-A Nos. 2006-309033, 2006-317560, 2006-328329, 2006-328334, 2006-337491, 2006-337492, 2006-337493, 2006-337569, and 2007-009182, and can be formed by the methods described in those publications.
[0039] In forming various polymers in acrylic resins, it is preferable to filter the monomer raw materials, auxiliary raw materials such as polymerization initiators and catalysts, and solvents used in polymerization as much as possible before use, from the viewpoint of reducing foreign matter in the polymer and because it can be filtered at a low viscosity stage rather than filtering after polymerization. As a filtering method, if it is a liquid, it can be directly filtered, and if it is a solid, it can be dissolved in the solvent used for polymerization and then passed through various filters such as membrane filters and hollow fiber membrane filters. They can be filtered separately or mixed and then filtered. In addition, the accuracy of filtration in this case is preferably 5.0 μm or less, more preferably 1.0 μm or less, and even more preferably 0.5 μm or less.
[0040] The acrylic resin may be composed of a combination of a (meth)acrylic polymer and another polymer depending on the desired physical properties, applications, etc. The other polymer is not particularly limited, and may be a thermoplastic polymer, a curable polymer, or a combination of these. The other polymer may be used alone or in combination of two or more kinds.
[0041] Specific examples of other polymers include another (meth)acrylic polymer having a different composition ratio or molecular weight from the (meth)acrylic polymer, or a different copolymer composition, an olefin-based polymer (e.g., polyethylene, polypropylene, ethylene-propylene copolymer, poly(4-methyl-1-pentene)), a halogen-based polymer (e.g., polyvinyl chloride, polyvinylidene chloride, polyvinyl chloride and other halogenated vinyl polymers), a styrene-based polymer [e.g., polystyrene, a styrene-based copolymer (e.g., styrene-methyl methacrylate copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer (ABS resin), acrylate-styrene-acrylonitrile copolymer (ASA resin)), etc.)], a polyester-based polymer (e.g., polyethylene terephthalate, polybutylene terephthalate, polyethylene Examples of the polymerizable compound include aromatic polyesters (e.g., aromatic polyesters such as phenyl naphthalate), polyamide polymers (e.g., aliphatic polyamide polymers such as polyamide 6, polyamide 66, and polyamide 610), polyacetal polymers, polycarbonate polymers, polyphenylene oxide polymers, polyphenylene sulfide polymers, polyether ether ketone polymers, polysulfone polymers, polyether sulfone polymers, copolymers having a polymer block having units derived from a diene and / or an olefin and a polymer block having units derived from an aromatic vinyl monomer [e.g., styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-butadiene / butylene-styrene block copolymer (SBS), etc.], cellulose polymers (cellulose derivatives), and thermoplastic elastomers (styrene-based elastomers, etc.).
[0042] When the acrylic resin contains other polymers in addition to the (meth)acrylic polymer, the form of the (meth)acrylic polymer and the other polymer is not particularly limited, and may be a polymer blend, or the above-mentioned (meth)acrylic polymer and the other polymer may be chemically bonded. In this case, the (meth)acrylic polymer and the other polymer may form a block copolymer, a graft copolymer, etc.
[0043] When the acrylic resin contains other polymers in addition to the (meth)acrylic polymer, the content of the other polymers is, for example, 90% by mass or less (e.g., 0.1 to 85% by mass), 80% by mass or less (e.g., 0.5 to 70% by mass), preferably about 60% by mass or less (e.g., 1 to 55% by mass), and may be 50% by mass or less (e.g., 2 to 45% by mass), 30% by mass or less (e.g., 2 to 25% by mass), 20% by mass or less (e.g., 2 to 15% by mass), etc.
[0044] For example, when the acrylic resin contains a styrene-based polymer, the acrylic resin film made of this acrylic resin can be made into a stretched film, so that the positive retardation exhibited by the (meth)acrylic polymer having a ring structure in the main chain can be cancelled by the negative retardation exhibited by the styrene-based polymer. By adjusting the content of the styrene-based polymer in the acrylic resin film, it is possible to make it into a negative retardation film or a polarizer protective film with a low retardation. When the acrylic resin film contains a styrene-based polymer, the styrene-based polymer is preferably a styrene-acrylonitrile copolymer from the viewpoint of compatibility with the (meth)acrylic polymer. When the acrylic resin film contains an ABS resin or an ASA resin, by adjusting the content of the ABS resin or the ASA resin in the acrylic resin film, it is possible to make the acrylic resin film into a negative retardation film or a film with a low retardation while increasing the flexibility.
[0045] The acrylic resin may contain materials other than the polymer, such as additives. The additives include, for example, antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; ultraviolet absorbers such as phenyl salicylate, (2,2'-hydroxy-5-methylphenyl)benzotriazole, and 2-hydroxybenzophenone; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents composed of anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic fillers; antiblocking agents; resin modifiers; organic fillers; inorganic fillers; plasticizers; lubricants; and retardation reducing agents.
[0046] The content of the additive in the acrylic resin is preferably 0 to 5% by weight, more preferably 0 to 2% by weight, and further preferably 0 to 0.5% by weight.
[0047] The Tg (glass transition temperature) of the acrylic resin is preferably 100° C. or higher, more preferably 110° C. or higher, even more preferably 115° C. or higher, and particularly preferably 120° C. or higher. There are no particular limitations on the upper limit of the Tg of the acrylic resin, but from the viewpoint of stretchability when made into an acrylic resin film, it is preferably 170° C. or lower.
[0048] The acrylic resin film is obtained by molding an acrylic resin. The thickness of the acrylic resin film is not particularly limited, but is preferably 5 to 200 μm, and more preferably 10 to 100 μm. When the thickness is 5 μm or more, the strength is excellent. When the thickness is 200 μm or less, the transparency is excellent.
[0049] The surface wet tension of the acrylic resin film is preferably 40 mN / m or more, more preferably 50 mN / m or more, and even more preferably 55 mN / m or more. When the surface wet tension is 40 mN / m or more, the adhesion between the optical film of this embodiment and other members is further improved. In order to adjust the surface wet tension, any appropriate surface treatment may be applied to the surface of the acrylic resin film. Examples of the surface treatment include corona discharge treatment, plasma treatment, ozone spraying, ultraviolet irradiation, flame treatment, and chemical treatment. Among these, corona discharge treatment and plasma treatment are preferred.
[0050] [Method of manufacturing (acrylic) resin film] The acrylic resin film can be formed by a known film-forming method using an acrylic resin. Examples of the film-forming method include a solution casting method, a melt extrusion method, a calendar method, and a compression molding method. Among them, the solution casting method and the melt extrusion method are preferable.
[0051] The acrylic resin used for film formation can be formed by a known method. For example, the acrylic resin is formed by thoroughly mixing the (meth)acrylic polymer, other thermoplastic polymers, and additives, etc., which are blended according to the composition of the acrylic resin to be obtained, by an appropriate mixing method. The mixing method is, for example, extrusion kneading or mixing in a solution state. A commercially available acrylic resin may be used for film formation. Examples of commercially available acrylic resins include ACRYPET VH and ACRYPET VRL20A (both manufactured by Mitsubishi Rayon). Any appropriate mixer, for example, an omnimixer, a single screw extruder, a twin screw extruder, or a pressure kneader, can be used for extrusion kneading.
[0052] The apparatus for carrying out the solution casting method is, for example, a drum-type casting machine, a band-type casting machine, or a spin coater. The solvent used in the solution casting method is not limited as long as it dissolves the acrylic resin. The solvent is, for example, aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as cyclohexane and decalin; esters such as ethyl acetate and butyl acetate; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; alcohols such as methanol, ethanol, isopropanol, butanol, isobutanol, methyl cellosolve, ethyl cellosolve, and butyl cellosolve; ethers such as tetrahydrofuran and dioxane; halogenated hydrocarbons such as dichloromethane, chloroform, and carbon tetrachloride; dimethylformamide; and dimethylsulfoxide. Two or more of these solvents may be used in combination.
[0053] The melt extrusion method is, for example, a T-die method or an inflation method. The molding temperature during melt extrusion is preferably 150 to 350°C, more preferably 200 to 300°C. In the T-die method, for example, a T-die is attached to the tip of a known extruder to form a strip-shaped acrylic resin film. The formed strip-shaped acrylic resin film may be wound around a roll to form a film roll.
[0054] The obtained acrylic resin film may be stretched. The stretching direction may be any of the longitudinal direction (MD direction) of the acrylic resin film, the width direction (TD direction) perpendicular to the longitudinal direction, and the oblique direction to the longitudinal direction. When stretching in biaxial directions, it may be sequential stretching in which stretching in the MD direction (longitudinal stretching) and stretching in the TD direction (transverse stretching) are performed sequentially, or simultaneous stretching in which stretching in the MD direction and stretching in the TD direction are performed simultaneously. The temperature during stretching is preferably within the range of (Tg-30) to (Tg+100)°C, more preferably within the range of (Tg-20) to (Tg+80)°C, and further preferably within the range of (Tg-5) to (Tg+20)°C, where Tg is the glass transition temperature of the acrylic resin film. The stretching ratio is not particularly limited, and may be, for example, about 1.1 to 25 times (for example, 1.3 to 10 times) as the maximum stretching ratio defined by the area ratio. The stretching speed (in one direction) is not particularly limited, but may be, for example, about 10 to 20,000% / min (for example, 100 to 10,000% / min). The stretched acrylic resin film is suitable as a retardation film. The stretching method is not particularly limited, and a known stretching machine can be used for stretching. The stretching machine will be described later.
[0055] When forming an acrylic resin film by melt extrusion, the process from forming the acrylic resin by mixing the materials to forming and stretching the acrylic resin film can be carried out continuously. When forming an acrylic resin film by the T-die method, it is also possible to simultaneously perform uniaxial stretching in the MD direction and winding the film by adjusting the temperature of the roll that winds up the formed film.
[0056] For example, after stretching, the acrylic resin film may be subjected to a heat treatment (annealing) in order to stabilize the optical isotropy and mechanical properties of the acrylic resin film. The method and conditions for the heat treatment can be appropriately selected.
[0057] [Easy adhesive layer] The easy-adhesion layer includes a binder resin, a polyamine, and fine particles. The polyamine is a polymer having a plurality of amino groups. The plurality of amino groups includes at least one selected from the group consisting of a secondary amino group and a tertiary amino group. The content of the polyamine in the easy-adhesion layer is 0.0090% by weight to 1.4100% by weight. The polyamine promotes the dispersion of the fine particles in the easy-adhesion layer, and improves the adhesion between the resin film and the easy-adhesion layer, the blocking resistance of the optical film, and the uniformity of the easy-adhesion layer.
[0058] The physical properties required for an optical film include retardation, tear resistance, folding resistance, etc. In order to obtain a biaxially stretched optical film that meets the required physical properties, it is necessary to strictly control the stretching temperature. The stretching temperature is changed according to subtle differences in the physical properties of each resin lot, such as molecular weight and composition ratio. Here, in the production of an optical film, the drying of the easy-adhesion layer is often performed simultaneously with the transverse stretching process. Therefore, changing the stretching temperature means changing the drying temperature of the easy-adhesion layer. When the alkali component contained in the easy-adhesion layer is a low-molecular-weight compound, changing the drying temperature of the easy-adhesion layer changes the amount of volatilization of the alkali component, and the content of the alkali component in the easy-adhesion layer also changes. In this case, there is a possibility that the desired effect based on the alkali component cannot be sufficiently obtained. It is difficult to change the stretching temperature to keep the content of the alkali component within the desired range. In particular, when an optical film is produced using a resin having a high Tg, such as an acrylic resin having a ring structure, it is necessary to increase the stretching temperature. A highly volatile low-molecular-weight alkali component is easily released to the outside during the stretching process at high temperatures. In this case, the effect of promoting the dispersion of the fine particles by the alkaline component becomes insufficient.
[0059] On the other hand, the polymer polyamine is difficult to volatilize and can remain reliably in the easy-adhesion layer. The content of the polyamine in the easy-adhesion layer is difficult to change even if the stretching temperature is changed. Therefore, the polymer polyamine is suitable for keeping the content of the alkali component in the easy-adhesion layer within a desired range, and can reliably promote the dispersion of the fine particles. As a result, the blocking resistance of the optical film can be further improved.
[0060] It is also presumed that the cationic nature of the polyamine acts on the ester moiety of the acrylic resin. In other words, it is presumed that the interaction between the amino group of the polyamine and the ester moiety of the acrylic resin improves the adhesion between the adhesive layer and the resin film.
[0061] In addition, when an acrylic resin having a ring structure in the main chain is used as the material of the resin film, the stretching temperature of the resin film (≒ drying temperature of the easy-adhesion layer) is set high. It is considered that the binder resin of the easy-adhesion layer easily penetrates into the surface of the resin film whose temperature is higher than Tg. As a result, the adhesion between the easy-adhesion layer and the resin film can be further improved.
[0062] The binder resin may be any known resin having good adhesive properties, such as urethane resin, cellulose resin, polyol resin, polycarboxylic acid resin, polyester resin, and acrylic resin. At least one selected from these resins can be used as the binder resin.
[0063] The number average molecular weight of the binder resin is preferably from 5,000 to 600,000, and more preferably from 10,000 to 400,000.
[0064] The binder resin includes, for example, a urethane resin. The binder resin is preferably a urethane resin. In this way, the adhesion of the easy-adhesion layer to the acrylic resin film is improved, and the easy-adhesion of the optical film to other members is improved.
[0065] The urethane resin is not particularly limited, and is typically a resin obtained by reacting a polyol with a polyisocyanate. The polyol may be any polyol having two or more hydroxyl groups in the molecule. The polyol may be, for example, a polyacrylic polyol, a polyester polyol, or a polyether polyol. Two or more types of polyols may be combined.
[0066] Polyacrylic polyol is typically a copolymer of a (meth)acrylic acid ester monomer and a monomer having a hydroxyl group. The (meth)acrylic acid ester monomer is, for example, methyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate. The monomer having a hydroxyl group is, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypentyl (meth)acrylate (meth)acrylic acid hydroxyalkyl ester; (meth)acrylic acid monoester of polyhydric alcohol such as glycerin and trimethylolpropane; and N-methylol (meth)acrylamide.
[0067] The polyacrylic polyol may be a copolymer with other monomers. The other monomers are not limited as long as they can be copolymerized with the above (meth)acrylic acid ester monomer and the monomer having a hydroxyl group. The other monomers are, for example, unsaturated monocarboxylic acids such as (meth)acrylic acid; unsaturated dicarboxylic acids such as maleic acid and their anhydrides and mono- or diesters; unsaturated nitriles such as (meth)acrylonitrile; unsaturated amides such as (meth)acrylamide and N-methylol (meth)acrylamide; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether; α-olefins such as ethylene and propylene; halogenated α,β-unsaturated aliphatic monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene.
[0068] The polyester polyol is typically obtained by reacting a polybasic acid component with a polyol component. Examples of the polybasic acid component include aromatic dicarboxylic acids such as orthophthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, and tetrahydrophthalic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, octadecanedicarboxylic acid, tartaric acid, alkylsuccinic acid, linoleic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, and itaconic acid; alicyclic dicarboxylic acids such as hexahydrophthalic acid, tetrahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and reactive derivatives thereof such as acid anhydrides, alkyl esters, and acid halides.
[0069] Examples of the polyol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1-methyl-1,3-butylene glycol, 2-methyl-1,3-butylene glycol, 1-methyl-1,4-pentylene glycol, 2-methyl-1,4-pentylene glycol, 1,2-dimethyl-neopentyl glycol, 2,3-dimethyl-neopentyl glycol, 1-methyl-1 ,5-pentylene glycol, 2-methyl-1,5-pentylene glycol, 3-methyl-1,5-pentylene glycol, 1,2-dimethylbutylene glycol, 1,3-dimethylbutylene glycol, 2,3-dimethylbutylene glycol, 1,4-dimethylbutylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediol, bisphenol A, bisphenol F, hydrogenated bisphenol A, and hydrogenated bisphenol F.
[0070] Polyether polyols are typically obtained by adding alkylene oxides to polyhydric alcohols through ring-opening polymerization. Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, glycerin, and trimethylolpropane. Examples of alkylene oxides include ethylene oxide, propylene oxide, butylene oxide, styrene oxide, and tetrahydrofuran.
[0071] Examples of the polyisocyanate include aliphatic diisocyanates such as tetramethylene diisocyanate, dodecamethylene diisocyanate, 1,4-butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, and 3-methylpentane-1,5-diisocyanate; isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-cyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, and 1,3-bis(isocyanate methyl)cycloisocyanate. alicyclic diisocyanates such as hexane; aromatic diisocyanates such as tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, and 1,4-phenylene diisocyanate; and aromatic aliphatic diisocyanates such as dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, and α,α,α,α-tetramethylxylylene diisocyanate.
[0072] The urethane resin preferably has a carboxyl group. The performance (easy adhesion) of the easy-adhesion layer is improved by having the carboxyl group. This effect is particularly remarkable under high temperature and high humidity environments. The urethane resin having a carboxyl group can be obtained, for example, by reacting a chain lengthener having a free carboxyl group with a polyol and a polyisocyanate. The chain lengthener having a free carboxyl group is, for example, a dihydroxycarboxylic acid or a dihydroxysuccinic acid. The dihydroxycarboxylic acid is, for example, a dialkylolalkanoic acid such as a dimethylolalkanoic acid (for example, dimethylolacetic acid, dimethylolbutanoic acid, dimethylolpropionic acid, dimethylolbutyric acid, dimethylolpentanoic acid).
[0073] The acid value of the urethane resin is preferably 10 or more, more preferably 10 to 50, and particularly preferably 20 to 45. In these cases, the performance of the easy-adhesion layer (for example, adhesion to other functional films such as a polarizer) is further improved.
[0074] The urethane resin may be obtained by reacting the above-mentioned components with other polyols or other chain extenders. The other polyols are, for example, polyols having three or more hydroxyl groups, such as sorbitol, 1,2,3,6-hexanetetraol, 1,4-sorbitan, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. Other chain lengthening agents include, for example, glycols such as ethylene glycol, diethylene glycol, triethylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 1,6-hexanediol, and propylene glycol; aliphatic diamines such as ethylenediamine, propylenediamine, hexamethylenediamine, 1,4-butanediamine, and aminoethylethanolamine; alicyclic diamines such as isophoronediamine and 4,4'-dicyclohexylmethanediamine; and aromatic diamines such as xylylenediamine and tolylenediamine.
[0075] The urethane resin can be formed by applying a known method. For example, the method is a one-shot method in which each component is reacted at once, or a multi-stage method in which the components are reacted stepwise. The urethane resin having a carboxyl group is preferably formed by the multi-stage method because the carboxyl group can be easily introduced. The catalyst used for forming the urethane resin is not particularly limited.
[0076] The polyamine may contain a primary amino group, a secondary amino group, and a tertiary amino group. Such a polyamine also exerts the effect of improving the adhesion between the resin film and the easy-adhesion layer.
[0077] The polyamine may contain a polyalkyleneimine. The polyalkyleneimine is suitable as an alkaline component of the easy-adhesion layer. The polyalkyleneimine may be linear or may have a branched structure.
[0078] As the polyamine, polyalkyleneimines are preferably used. Examples of the polyalkyleneimines include polyalkyleneimines obtained by polymerizing one or more alkyleneimines having 2 to 6 carbon atoms, and derivatives obtained by adding unsaturated carboxylic acid or alkylene oxide to polyalkyleneimines. Examples of the alkyleneimines having 2 to 6 carbon atoms include ethyleneimine, propyleneimine, 1,2-butyleneimine, 2,3-butyleneimine, and 1,1-dimethylethyleneimine. Examples of the polyalkyleneimines include polyethyleneimine, polypropyleneimine, polyethyleneimine derivatives, and polypropyleneimine derivatives, and more preferably polyethyleneimine and polyethyleneimine derivatives. Examples of the polyethyleneimine and polyethyleneimine derivatives include the commercially available Epomin series manufactured by Nippon Shokubai Co., Ltd., such as Epomin SP-003, Epomin SP-006, Epomin SP-012, Epomin SP-018, Epomin SP-103, Epomin SP-110, Epomin SP-200, Epomin SP-300, Epomin SP-1000, and Epomin SP-1020 (all of which are trade names).
[0079] The polyalkyleneimine contains a primary amino group, a secondary amino group, and a tertiary amino group, and may have a branched structure. The polyalkyleneimine having such a structure is suitable as an alkaline component of the easy-adhesion layer.
[0080] By adjusting the content of the polyamine in the adhesion layer to the above range, the adhesion between the resin film and the adhesion layer can be improved. The content of the polyamine in the adhesion layer may be 0.0098% by weight to 1.4098% by weight.
[0081] The presence and content of polyamine in the adhesive layer can be examined by known analytical methods such as NMR.
[0082] The fine particles may be either inorganic fine particles or organic fine particles. The inorganic fine particles are, for example, inorganic oxides such as silica, titania, alumina, and zirconia; calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate. The organic fine particles are, for example, fine particles of silicone resin, fluorine resin, and acrylic resin. Among them, silica fine particles are preferable. Silica fine particles improve blocking resistance. In addition, silica fine particles have excellent transparency, so that coloring and an increase in haze ratio of the optical film are unlikely to occur.
[0083] The particle diameter (average particle diameter) of the fine particles is preferably 10 to 1000 nm. By using fine particles with such a particle diameter, appropriate unevenness can be formed on the surface of the easy-adhesion layer, and blocking between the acrylic resin film and the easy-adhesion layer, or between the easy-adhesion layers themselves, can be effectively reduced. The average particle diameter of the fine particles is smaller than the visible light wavelength from the viewpoint of suppressing light scattering by the particles, and the smaller the better, but from the viewpoint of blocking properties, the larger the better. For this reason, the upper limit of the average particle diameter is, for example, 900 nm or less, 800 nm or less, 700 nm or less, or 600 nm or less, more preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 350 nm or less. The lower limit is 20 nm or more, 40 nm or more, 60 nm or more, 80 nm or more, 100 nm or more, more preferably 120 nm or more, 140 nm or more, 160 nm or more, 180 nm or more, 200 nm or more, and more preferably 220 nm or more, 240 nm or more, 260 nm or more, 280 nm or more, 300 nm or more, 320 nm or more, 340 nm or more. The particle size distribution of the fine particles is preferably 1.0 to 1.2.
[0084] The content of the fine particles in the easy-adhesion layer is not particularly limited, but the upper limit of the content is preferably less than 30 parts by weight, more preferably less than 20 parts by weight, and even more preferably less than 5 parts by weight, relative to 100 parts by weight of the binder resin (solid content: solid content including the crosslinking agent if a crosslinking agent is included). When the content of the fine particles is less than 30 parts by weight, the strength of the easy-adhesion layer is excellent. The lower limit of the content is preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, and even more preferably 0.5 parts by weight or more. When the content of the fine particles is 0.1 parts by weight or more, the blocking resistance of the optical film is excellent. Note that, when the average particle diameter is small (for example, less than 100 nm), the content of the fine particles is preferably high in order to obtain the effect of improving the blocking resistance, and the lower limit of the content is preferably 0.5 parts by weight or more, 1.0 parts by weight or more, 5.0 parts by weight or more, or 10.0 parts by weight or more. Furthermore, if the average particle size is large (eg, 200 nm or more), the fine particle content is better to be small from the viewpoint of suppressing light scattering, and the upper limit of the content is preferably less than 2.0 parts by weight, and more preferably less than 1.0 part by weight.
[0085] The thickness of the easy-adhesion layer is not limited and varies depending on the thickness of the film, but is preferably 100 nm to 10 μm, more preferably 100 nm to 5 μm, and even more preferably 200 nm to 1.5 μm. In this range, the easy-adhesion layer provides good adhesion to other members of the optical film. In addition, the easy-adhesion layer itself can be prevented from generating retardation.
[0086] The ratio r / d of the thickness d of the adhesive layer to the average particle size r of the fine particles contained in the adhesive layer is preferably 0.3 to 1.4, more preferably 0.4 to 1.1, and even more preferably 0.6 to 1.0. Within this range, the optical film of the present embodiment can more reliably achieve both blocking resistance and transparency.
[0087] The method of forming the easy-adhesion layer on the surface of the optical film is not limited, and may be any known method. The easy-adhesion layer is preferably formed by applying an easy-adhesion composition containing a binder resin, a polyamine, and fine particles to the surface of the resin film to form a coating film of the easy-adhesion composition, and drying the coating film. The easy-adhesion composition is preferably a water-based composition. Compared with organic solvent-based compositions, water-based compositions have a smaller environmental load when forming the easy-adhesion layer and are excellent in workability. The water-based composition is, for example, a dispersion of a binder resin. The dispersion is typically an emulsion of a binder resin. The emulsion of the binder resin becomes a resin layer by drying. The fine particles contained in the emulsion remain in the resin layer as they are.
[0088] When the adhesive composition is water-based, the fine particles are preferably blended as a water dispersion such as colloidal silica. The colloidal silica may be a commercially available product as long as the average particle size and particle size distribution are within the above-mentioned ranges.
[0089] When the easy-adhesion composition is an aqueous composition containing a urethane resin, it is preferable to use an organic solvent that is inactive to polyisocyanate and compatible with water when forming the urethane resin. The organic solvent is, for example, an ester solvent such as ethyl acetate, butyl acetate, or ethyl cellosolve acetate; a ketone solvent such as acetone, methyl ethyl ketone, or methyl isobutyl ketone; or an ether solvent such as dioxane, tetrahydrofuran, or propylene glycol monomethyl ether.
[0090] When the easy-adhesion composition contains a urethane resin, the performance of the easy-adhesion layer is improved by further containing a crosslinking agent. The crosslinking agent is not particularly limited. When the urethane resin has a carboxyl group, the crosslinking agent is preferably a polymer having a group capable of reacting with the carboxyl group. The group capable of reacting with the carboxyl group is, for example, an organic amino group, an oxazoline group, an epoxy group, or a carbodiimide group, and an oxazoline group is preferable. A crosslinking agent having an oxazoline group has a long pot life at room temperature when mixed with a urethane resin, and the crosslinking reaction proceeds by heating, so that the workability is good. The polymer is, for example, a (meth)acrylic polymer or a styrene-acrylic polymer, and a (meth)acrylic polymer is preferable. When the crosslinking agent is a (meth)acrylic polymer, the performance of the easy-adhesion layer is further improved. In addition, the (meth)acrylic polymer is stably compatible with the water-based easy-adhesion composition and crosslinks the urethane resin well.
[0091] When the adhesive composition contains a urethane resin, the content of the urethane resin is preferably 1.5 to 15% by weight, more preferably 2 to 10% by weight. When the content is within these ranges, the adhesive composition has high applicability when applied to the surface of an optical film, particularly an acrylic resin film. When the composition further contains a crosslinking agent, the content of the crosslinking agent is preferably 1 to 30 parts by weight, more preferably 3 to 20 parts by weight, based on 100 parts by weight of the urethane resin (solid content).
[0092] When the easy-adhesion composition contains a urethane resin, it is preferable to contain a neutralizing agent. In this case, the stability of the urethane resin in the easy-adhesion composition is improved. The neutralizing agent is, for example, ammonia, N-methylmorpholine, triethylamine, dimethylethanolamine, methyldiethanolamine, triethanolamine, morpholine, tripropylamine, ethanolamine, triisopropanolamine, and 2-amino-2-methyl-1-propanol.
[0093] The adhesive composition may contain additives such as a dispersion stabilizer, a thixotropic agent, an antioxidant, an ultraviolet absorber, a defoamer, a thickener, a dispersant, a surfactant, a catalyst, and an antistatic agent.
[0094] [Optical film characteristics and applications] The optical film of the present embodiment has excellent adhesion to other members and blocking resistance. It also has excellent transparency and usually has a haze ratio of 1.5% or less. Depending on the configuration of the optical film of the present embodiment, the haze ratio is 1.0% or less, or even 0.5% or less.
[0095] The optical film of this embodiment is, for example, a polarizer protection film, a retardation film, a viewing angle compensation film, a light diffusion film, a reflection film, an anti-reflection film, an anti-glare film, a brightness improvement film, or a conductive film for a touch panel. The retardation exhibited by the optical film of this embodiment can be controlled by the composition and stretching state of the film. The optical film of this embodiment can be an optically isotropic film, or a film having optical anisotropy (for example, a film that exhibits birefringence such as retardation).
[0096] When the optical film of the present embodiment is used as a retardation film, it is suitable for use in an image display device such as an LCD, etc. The retardation film can be used, for example, for color compensation and viewing angle compensation of the LCD.
[0097] Since the retardation film has an easy-adhesion layer, it can be used in a form other than that usually used as a retardation film. Specifically, for example, it can be used by bonding to a polarizer equipped in an LCD. In this case, the retardation film has a function as a normal retardation film for color tone compensation or viewing angle compensation, as well as a function as a polarizer protective film that protects the polarizer. This form is advantageous for making the LCD thinner and more functional because it can omit a polarizer protective film that does not have a retardation, which has been used separately from the retardation film in the past.
[0098] When the easy-adhesion layer is formed only on one surface of the optical film, various functional coating layers may be formed on the opposite surface as necessary. Examples of the functional coating layer include an antistatic layer, a pressure-sensitive adhesive layer, an adhesive layer, an easy-adhesion layer, an antiglare layer, an antifouling layer such as a photocatalyst layer, an antireflection layer, a hard coat layer, an ultraviolet shielding layer, a heat ray shielding layer, an electromagnetic wave shielding layer, and a gas barrier layer.
[0099] [Optical components] The optical film of the present embodiment is suitable for optical members such as polarizing plates, diffusion plates, light guides, and prism sheets.
[0100] A polarizing plate will be described as an example of the optical member of the present embodiment. In an LCD, a pair of polarizing plates are arranged to sandwich a liquid crystal cell based on the image display principle. The polarizing plate has a structure in which the optical film of the present embodiment (polarizer protective film) is laminated on at least one surface of a polarizer via an easy-adhesion layer, for example.
[0101] Conventionally, triacetyl cellulose (TAC) films have been used as polarizer protective films. However, TAC films do not have sufficient moist heat resistance, and when a TAC film is used as a polarizer protective film, the properties of the polarizing plate may deteriorate under high temperature or high humidity environments. In addition, TAC films have a retardation in the thickness direction, which adversely affects the viewing angle properties of image displays such as LCDs, particularly large-screen image displays. In contrast, it is preferable to use an acrylic resin film as a polarizer protective film, since it can improve moist heat resistance and optical properties compared to TAC films.
[0102] A polarizing plate is typically produced by laminating an optical film and a polarizer via an adhesive layer. When the optical film has an easy-adhesion layer, the two are laminated so that the easy-adhesion layer is on the polarizer side. Specifically, for example, an adhesive composition that will become an adhesive layer after drying is applied to the surface of either the polarizer or the optical film, and then the two are laminated and dried. The adhesive composition is applied by, for example, a roll method, a spray method, or a dipping method. When the adhesive composition contains a metal compound colloid, the adhesive composition is applied so that the thickness of the adhesive layer after drying is larger than the average particle diameter of the metal compound colloid particles. The drying temperature is typically 5 to 150°C, preferably 30 to 120°C. The drying time is typically 120 seconds or more, preferably 300 seconds or more.
[0103] The polarizer is not limited, and any appropriate polarizer can be adopted depending on the function required as a polarizing plate. The polarizer is, for example, a film obtained by uniaxially stretching a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or a partially saponified film of an ethylene-vinyl acetate copolymer (EVA) after adsorbing a dichroic substance such as iodine or a dichroic dye; or a polyene-based oriented film using a dehydrated product of PVA or a dehydrochlorinated product of polyvinyl chloride. Among them, a film obtained by adsorbing a dichroic substance to a PVA film and uniaxially stretching is preferable as a polarizer. This polarizer shows a high polarization dichroic ratio. The thickness of the polarizer is not limited, and is generally about 1 to 80 μm. A polarizer obtained by adsorbing iodine to a PVA film and uniaxially stretching it can be produced, for example, by immersing a PVA film in an aqueous solution containing iodine to dye it, and uniaxially stretching it at a stretching ratio of 3 to 7 times. The aqueous solution used for dyeing may contain boric acid, zinc sulfate, zinc chloride, etc. as necessary. As the aqueous solution containing iodine, an aqueous solution of an iodide such as potassium iodide may be used. The PVA-based film may be immersed in water and washed before dyeing. By washing the PVA-based film with water, dirt and antiblocking agents present on the surface of the film can be removed. Furthermore, since the PVA-based film swells by washing with water, unevenness during dyeing is suppressed. Stretching may be performed before dyeing, after dyeing, or simultaneously with dyeing.
[0104] The adhesive composition that becomes the adhesive layer after drying is not limited. The adhesion method is not limited, and may be water glue or UV adhesion. The adhesive composition preferably contains a PVA-based resin. The PVA-based resin includes, for example, the following polymers: saponification products of polyvinyl acetate and its derivatives; saponification products of copolymers of vinyl acetate and other monomers; modified PVA obtained by acetalization, urethanization, etherification, grafting, or phosphorylation of PVA. The other monomers are, for example, unsaturated carboxylic acids and their esters, such as (anhydride) maleic acid, fumaric acid, crotonic acid, itaconic acid, and (meth)acrylic acid; α-olefins, such as ethylene and propylene; (meth)allylsulfonic acid (soda), sodium sulfonate (monoalkyl maleate), sodium disulfonate alkyl maleate, N-methylol acrylamide, alkali salts of acrylamido alkyl sulfonates, N-vinyl pyrrolidone, and N-vinyl pyrrolidone derivatives. The PVA-based resin preferably contains an acetoacetyl group-containing PVA. In this case, the adhesion between the polarizer and the optical film (particularly the acrylic resin film) is improved, and the durability of the polarizing plate is improved.
[0105] From the viewpoint of adhesiveness of the adhesive composition, the average polymerization degree of the PVA-based resin is preferably about 100 to 5000, and more preferably 1000 to 4000. From the viewpoint of adhesiveness of the adhesive composition, the average saponification degree of the PVA-based resin is preferably about 85 to 100 mol%, and more preferably 90 to 100 mol%.
[0106] Acetoacetyl group-containing PVA can be obtained, for example, by reacting PVA with diketene by any method. Specific examples include a method of adding diketene to a dispersion of PVA in a solvent such as acetic acid, a method of adding diketene to a solution of PVA in a solvent such as dimethylformamide or dioxane, and a method of directly contacting PVA with diketene gas or liquid diketene.
[0107] The degree of modification of the acetoacetyl group-containing PVA is typically 0.1 mol% or more, preferably 0.1 to 40 mol%, more preferably 1 to 20%, and further preferably 2 to 7 mol%. By appropriately adjusting the degree of modification, the effect of modification (e.g., improvement of water resistance) can be sufficiently obtained. The degree of modification of the PVA with acetoacetyl groups can be measured by NMR.
[0108] The adhesive composition may contain a crosslinking agent. The crosslinking agent is not limited, but is a compound having at least two functional groups that show reactivity with the PVA-based resin. Examples of the crosslinking agent include alkylene diamines having an alkylene group and two amino groups, such as ethylene diamine, triethylene diamine, and hexamethylene diamine; isocyanates such as tolylene diisocyanate, hydrogenated tolylene diisocyanate, trimethylolpropane tolylene diisocyanate adduct, triphenylmethane triisocyanate, methylene bis(4-phenylmethane triisocyanate), isophorone diisocyanate, and ketoxime-blocked or phenol-blocked products thereof; ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, and the like. Epoxies such as ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, and diglycidyl amine; monoaldehydes such as formaldehyde, acetaldehyde, propionaldehyde, and butylaldehyde; dialdehydes such as glyoxal, malondialdehyde, succindialdehyde, glutaric dialdehyde, maleic dialdehyde, and phthalic dialdehyde; amino-formaldehyde resins such as methylol urea, methylol melamine, alkylated methylol urea, alkylated methylol melamine, acetoguanamine, and condensates of benzoguanamine and formaldehyde; and salts and oxides of monovalent to trivalent metals such as sodium, potassium, magnesium, calcium, aluminum, iron, and nickel. Among these, the crosslinking agent is preferably an amino-formaldehyde resin or a dialdehyde. The amino-formaldehyde resin preferably has a methylol group, and is preferably methylolmelamine.The dialdehyde is preferably glyoxal.
[0109] The amount of the crosslinking agent in the adhesive composition can be appropriately set according to the type of PVA resin. Typically, it is about 10 to 60 parts by weight, preferably 20 to 50 parts by weight, per 100 parts by weight of the PVA resin. In this range, good adhesion can be obtained. By appropriately adjusting the amount of the crosslinking agent, gelation of the adhesive composition can be suppressed. In this case, the usable time (pot life) of the adhesive composition is extended, making industrial use easier.
[0110] The adhesive composition may contain a metal compound colloid. The metal compound colloid may be a colloid in which particles of a metal compound are dispersed in a dispersion medium. The metal compound colloid may be a colloid that has permanent stability due to electrostatic stabilization caused by mutual repulsion of the same type of charge of the particles. By containing the metal compound colloid in the adhesive composition, the stability of the adhesive composition is improved, for example, even when the amount of the crosslinking agent is large.
[0111] The average particle size of the colloidal particles in the metal compound colloid can be set within a range that does not adversely affect the optical properties (e.g., polarization properties) of the polarizing plate. The average particle size of the colloidal particles is preferably 1 to 100 nm, more preferably 1 to 50 nm. Within these ranges, the colloidal particles can be uniformly dispersed in the adhesive layer. This ensures adhesion and suppresses the occurrence of knick defects. If knick defects occur, for example, light leakage occurs in an image display device incorporating the polarizing plate.
[0112] The metal compound is not limited, and examples thereof include oxides such as alumina, silica, zirconia, and titania; metal salts such as aluminum silicate, calcium carbonate, magnesium silicate, zinc carbonate, barium carbonate, and calcium phosphate; and minerals such as celite, talc, clay, and kaolin. A metal compound colloid having a positive charge is preferred. The metal compound that becomes a colloid having a positive charge is preferably alumina or titania, and particularly preferably alumina.
[0113] The metal compound colloid is typically a colloidal solution dispersed in a dispersion medium. The dispersion medium is, for example, water or alcohol. The solid content concentration in the colloidal solution is typically about 1 to 50% by weight, and preferably 1 to 30% by weight. The colloidal solution may contain an acid such as nitric acid, hydrochloric acid, or acetic acid as a stabilizer.
[0114] The amount of the metal compound colloid in the adhesive composition (converted into solid content) is preferably 200 parts by weight or less, more preferably 10 to 200 parts by weight, further preferably 20 to 175 parts by weight, and particularly preferably 30 to 150 parts by weight, per 100 parts by weight of the PVA-based resin. Within these ranges, the adhesive composition has a more reliable adhesiveness while further suppressing the occurrence of knick defects.
[0115] The adhesive composition may contain coupling agents such as silane coupling agents and titanium coupling agents; various tackifiers; ultraviolet absorbers; antioxidants; and stabilizers such as heat stabilizers and hydrolysis-resistant stabilizers.
[0116] The adhesive composition is preferably an aqueous solution (resin solution). The concentration of the resin in the aqueous solution is preferably 0.1 to 15% by weight, more preferably 0.5 to 10% by weight, from the viewpoint of the coatability and shelf stability of the composition. The viscosity of the aqueous solution is preferably 1 to 50 mPa·s. When the adhesive composition contains a metal compound colloid, even if the adhesive composition has a low viscosity of 1 to 20 mPa·s, the occurrence of knick defects is effectively suppressed. The pH of the aqueous solution is preferably 2 to 6, more preferably 2.5 to 5, even more preferably 3 to 5, and particularly preferably 3.5 to 4.5. In general, the surface charge of the metal compound colloid is adjusted by adjusting the pH of the aqueous solution. The surface charge is preferably a positive charge. The positive charge further suppresses the occurrence of knick defects. The surface charge of the metal compound colloid can be confirmed, for example, by measuring the zeta potential with a zeta potential measuring device.
[0117] The adhesive composition, which is an aqueous solution (resin solution), can be formed by a known method. When the adhesive composition contains a crosslinking agent and a metal compound colloid, for example, a method can be used in which a PVA resin and a crosslinking agent are mixed together and adjusted to an appropriate concentration, and then the metal compound colloid is blended into the solution. After mixing the PVA resin and the metal compound colloid, the crosslinking agent may be mixed in while taking into consideration the time of use of the adhesive composition. The concentration of the aqueous solution can be adjusted after the aqueous solution is prepared.
[0118] The thickness of the adhesive layer formed from the adhesive composition can be appropriately set depending on the composition of the composition. The thickness is preferably 10 to 300 nm, more preferably 10 to 200 nm, and particularly preferably 20 to 150 nm. Within this range, the adhesive layer exhibits sufficient adhesive strength.
[0119] [Image display device] The optical film of the present embodiment is suitable for image display devices such as electroluminescence (EL) display panels, plasma display panels (PDPs), field emission displays (FEDs), LCDs, etc. The configuration of an image display device including the optical film of the present embodiment is not particularly limited, and it is sufficient to include components such as a power source, a backlight unit, and an operation unit as necessary.
[0120] [Method of manufacturing optical film] The method for producing the optical film includes a step of applying an easy-adhesion composition containing a binder resin, a polyamine, and fine particles to the surface of a resin film to form a coating film of the easy-adhesion composition (coating step), and a step of drying the formed coating film to form an easy-adhesion layer on the surface of the resin film (drying step).The method for producing the resin film is as described above.
[0121] In the coating step, a coating film of the easy-adhesion composition is formed on at least one surface of the resin film. Typically, the coating film is formed on one surface of the optical film. A known method can be applied as a method for coating the easy-adhesion composition in the coating step.
[0122] The method is, for example, a bar coating method, a roll coating method, a gravure coating method, a rod coating method, a slot orifice coating method, a curtain coating method, a fountain coating method, etc. The thickness of the coating film formed in the coating step can be appropriately adjusted depending on the thickness required when the coating film becomes an easily adhesive layer.
[0123] The surface of the resin film to which the adhesive composition is applied is preferably subjected to a surface treatment. The surface treatment is as described above, but corona discharge treatment and plasma treatment are preferred. The conditions for the corona discharge treatment are not limited. The electron irradiation dose in the corona discharge treatment is 50 to 150 W / m 2 / min is preferred, 70-100W / m 2 / min is more preferred.
[0124] A known method can be used for the drying step. The drying temperature is typically 50° C. or higher, preferably 90° C. or higher, and more preferably 110° C. or higher. By setting the drying temperature within these ranges, for example, an optical film having excellent corrosion resistance (particularly in a high-temperature and high-humidity environment) can be obtained. The upper limit of the drying temperature is preferably 200° C. or lower, and more preferably 180° C. or lower.
[0125] The resin film may be stretched between the coating step and the drying step, simultaneously with the drying step, or after the drying step. The resin film after the easy-adhesion composition is applied can be stretched by a known method, and can be uniaxially or biaxially stretched in the same manner as the stretching method of the resin film (before the easy-adhesion layer is applied) described above.
[0126] The resin film forming the coating film of the easy-adhesion composition in the coating process may be an unstretched resin film or a stretched resin film.When the resin film before the coating process is an unstretched film and the optical film finally produced is a biaxially stretched film, it may be biaxially stretched after the coating process.When the resin film before the coating process is a uniaxially stretched film and the optical film finally produced is a biaxially stretched film, it may be uniaxially stretched in the MD direction and stretched in the TD direction after the coating process.
[0127] A known stretching machine can be used to stretch the resin film. The longitudinal stretching machine is not particularly limited, but an oven stretching machine is preferred. The oven longitudinal stretching machine is generally composed of an oven and a conveying roll provided at the entrance side and the exit side of the oven. The resin film is stretched in the conveying direction by providing a peripheral speed difference between the conveying roll at the entrance side of the oven and the conveying roll at the exit side. The transverse stretching machine is not particularly limited, but a tenter stretching machine is preferred. The tenter stretching machine may be of a grip type or a pin type, but the grip type is preferred because the resin film is less likely to tear. The grip type tenter stretching machine is generally composed of a clip running device for transverse stretching and an oven. In the clip running device, the resin film is transported with the transverse end of the resin film being clamped by clips. At this time, the guide rail of the clip running device is opened and the distance between the two rows of clips on the left and right is widened, so that the resin film is transversely stretched. In the grip-type tenter stretching machine, simultaneous biaxial stretching is possible by providing the clip with an expansion / contraction function in the transport direction of the resin film. Alternatively, the machine may be an oblique stretching machine that tensilely stretches the resin film in the transport direction of the film at different speeds on the left and right sides of the stretching direction.
[0128] The stretching temperature is preferably near the Tg of the resin constituting the resin film. Specifically, the temperature is preferably in the range of Tg-30° C. to Tg+100° C., and more preferably in the range of Tg-20° C. to Tg+80° C. By appropriately adjusting the stretching temperature, a stable and sufficient stretch ratio can be achieved.
[0129] The stretching ratio defined by the area ratio is preferably 1.1 to 25 times, more preferably 1.3 to 10 times. By appropriately adjusting the stretching ratio, the properties (e.g., toughness) of the optical film can be improved. The stretching speed is preferably 10 to 20,000% / min, more preferably 100 to 10,000% / min for stretching in one direction. By appropriately adjusting the stretching speed, the time required for stretching can be shortened while preventing breakage of the optical film.
[0130] When the formation of the easy-adhesion layer and the stretching of the resin film are performed simultaneously, for example, after the coating step, the resin film on which the coating film of the easy-adhesion composition is formed may be stretched under a heated atmosphere. The coating film of the easy-adhesion composition formed on the surface of the resin film is dried by the heat applied to the resin film for stretching, and becomes an easy-adhesion layer. Since the Tg of the resin film is usually 100°C or higher, the stretching temperature described above is a temperature high enough to form an easy-adhesion layer from the coating film of the easy-adhesion composition.
[0131] When the resin film is formed by melt extrusion, the steps from the formation of the resin film to obtaining an optical film that is a stretched film can be performed continuously. In this case, it is preferable to continuously perform the step of applying an easy-adhesion composition to the surface of the resin film and the step of stretching the film coated with the easy-adhesion composition under a heated atmosphere. Such a step of applying the easy-adhesion composition that is performed continuously is called in-line coating. When an optical film that is a biaxially stretched film is produced by the production method of this embodiment, it is particularly preferable to continuously perform the step of stretching an unstretched film to obtain a uniaxially stretched film, the step of applying an easy-adhesion composition to the surface of the film, and the step of stretching the film coated with the easy-adhesion composition under a heated atmosphere. Furthermore, when performing surface treatment such as corona discharge treatment and plasma treatment on the film, it is preferable to continuously perform the step of stretching an unstretched film to obtain a uniaxially stretched film, the step of surface-treating the surface of the film, the step of applying an easy-adhesion composition to the surface of the surface-treated film, and the step of stretching the film coated with the easy-adhesion composition under a heated atmosphere.
[0132] The manufacturing method of the present embodiment may include any step other than the steps described above, such as a step of laminating an additional layer (e.g., a resin layer) on the formed optical film, or a step of subjecting the formed optical film to post-processing such as coating or surface treatment. EXAMPLES
[0133] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0134] (1) Analysis method (1-1) Weight average molecular weight (Mw) The weight average molecular weight was determined in terms of polystyrene using gel permeation chromatography (GPC) using the following apparatus and conditions: -System: Tosoh GPC system HLC-8220 - Measurement column configuration Guard column: Tosoh Corporation, TSKguardcolumn SuperHZ-L Separation column: Tosoh Corporation, TSKgel SuperHZM-M, 2 columns connected in series -Reference column configuration Reference column: Tosoh Corporation, TSKgel SuperH-RC -Developing solvent: Chloroform (Wako Pure Chemical Industries, special grade) -Flow rate of developing solvent: 0.6mL / min -Standard sample: TSK standard polystyrene (Tosoh Corporation, PS-oligomer kit) -Column temperature: 40℃
[0135] (1-2) Glass transition temperature (Tg) The glass transition temperature was determined in accordance with the provisions of Japanese Industrial Standard JIS K7121. Specifically, a differential scanning calorimeter (Rigaku Thermo plus EVO DSC-8230) was used to evaluate the glass transition temperature by the starting point method from the DSC curve obtained by heating about 10 mg of a sample from room temperature to 200°C (heating rate 20°C / min) under a nitrogen gas atmosphere. α-alumina was used as the reference.
[0136] (1-3) Optical film thickness The thickness of the optical film was measured using a Digimatic Micrometer (manufactured by Mitutoyo Corporation). Samples for measuring and evaluating the physical properties of the optical film, including the physical properties for which the evaluation methods will be shown below, were taken from the center of the film in the width direction.
[0137] (1-4) Average particle size and particle size distribution of fine particles Silica particles were added to methanol to a concentration of 1% by mass, and dispersed for 10 minutes using an ultrasonic disperser to prepare a measurement sample. This sample was measured using a laser diffraction / scattering particle size distribution measuring device (LA-920, manufactured by Horiba, Ltd.). The arithmetic mean value of the obtained volume-based particle size distribution was taken as the average particle size, and the arithmetic maximum value was taken as the maximum particle size.
[0138] (1-5) Total light transmittance, haze The total light transmittance, haze (total haze), and internal haze of the prepared optical film were measured using a turbidity meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.) based on the provisions of JIS K7136. Note that the internal haze was measured in a state where the film to be measured was immersed in tetralin in a quartz cell.
[0139] (1-6) Adhesion between resin film and adhesive layer The adhesion between the prepared resin film and the easy-adhesion layer was evaluated by a cross-section test in accordance with JIS K5400 3.5, as follows. A 1 mm square cross-section was made on the easy-adhesion layer surface of the test sample in three places with a sharp blade. Cellophane tape (24 mm wide, JIS Z1522) was attached to the cuts with a wooden spatula. The cellophane tape was then peeled off, and the presence or absence of peeling of the easy-adhesion layer was confirmed. If the easy-adhesion layer did not peel off, new cellophane tape was again attached to the cuts with a wooden spatula, and the cellophane tape was peeled off, and the adhesion was evaluated. This evaluation was performed in three places. The evaluation criteria are as follows. ⊚: The easy-adhesion layer did not peel off at three out of three locations even after five peel tests. ◯: The easy-adhesion layer did not peel off at one or two of the three locations even after five peel tests. ×: The easy-adhesion layer peeled off at three out of three locations during one to four peel tests.
[0140] (1-7) Blocking resistance of optical films The blocking resistance of the prepared optical film was evaluated as follows. The prepared optical film was wound on a roll to form a film roll, which was then left for 24 hours. After leaving it, the film roll was visually inspected, and the optical film was unwound from the film roll while visually inspecting the surface of the optical film over the entire longitudinal direction to evaluate the blocking resistance. The evaluation criteria were as follows: ◯: No deformation of the film roll and no wrinkles in the unwound optical film were observed. ×: Deformation of the film roll or wrinkles in the unwound optical film were observed.
[0141] (1-8) Uniformity of adhesive layer The prepared adhesive composition (coating liquid) was also applied to a resin film and dried to obtain an adhesive layer (coating film), which was visually observed to evaluate the uniformity of the adhesive composition and the uniformity of the adhesive layer. The evaluation criteria were as follows, and were shown as (evaluation of the adhesive composition) / (evaluation of the adhesive layer). Regarding the evaluation of the easy-adhesion composition, A: When a uniform, easily adhesive composition is easily obtained. B: When the adhesive composition was prepared, non-uniform substances such as gel fractions were observed, but a uniform adhesive composition was obtained by stirring for less than 6 hours. C: When preparing the adhesive composition, non-uniform substances such as gel fractions were observed, but a uniform adhesive composition could not be obtained without filtration.
[0142] Regarding the evaluation of the easy-adhesion layer, A: When no uneven coating, streaks or thickness irregularities can be visually detected and a uniform coating film has been obtained. B: At least one of the following is visually confirmed: uneven coating, streaks, or uneven thickness, and a uniform coating film has not been obtained.
[0143] (2) Manufacturing example (Production Example 1) A 1000L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube and a nitrogen inlet tube was charged with 40 parts by weight of methyl methacrylate (MMA), 10 parts by weight of 2-(hydroxymethyl)methyl acrylate (MHMA), 50 parts by weight of toluene as a polymerization solvent and 0.025 parts by weight of an antioxidant (ADEKA STAB 2112, manufactured by ADEKA), and the temperature was raised to 105°C while nitrogen was passed through the reaction vessel. When refluxing with the temperature increase started, 0.05 parts by weight of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi, trade name: Luperox 570) was added as a polymerization initiator, and 0.10 parts by weight of the above t-amyl peroxy isononanoate was added dropwise over 3 hours, while solution polymerization was allowed to proceed under reflux at about 105 to 110°C, and the mixture was further aged for 4 hours.
[0144] Next, 0.05 parts by weight of 2-ethylhexyl phosphate (Phoslex A-8, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained polymerization solution as a catalyst (cyclization catalyst) for the cyclization condensation reaction, and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed for 2 hours under reflux at about 90 to 110° C. Next, the obtained polymerization solution was heated to 240° C. using an autoclave, and the cyclization condensation reaction was allowed to proceed further at that temperature.
[0145] Next, the obtained polymerization solution was passed through a separatory separator having a barrel temperature of 240°C, a rotation speed of 100 rpm, a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), one rear vent and four fore vents (referred to as the first, second, third, and fourth vents from the upstream side), a side feeder provided between the third and fourth vents, and a leaf disk-type polymer filter (filtration accuracy 5 μm, filtration area 1.5 m) at the tip. 2 The mixture was introduced into a vent-type twin-screw extruder (φ=50.0 mm, L / D=30) equipped with a vent-type screw extruder (φ=50.0 mm, L / D=30) at a processing rate of 45 kg / hour (resin amount equivalent) and devolatilization was performed. At that time, a mixed solution of antioxidant / cyclization catalyst deactivator that had been separately prepared was added at a rate of 0.68 kg / hour from behind the first vent, and ion-exchanged water was added at a rate of 0.22 kg / hour from behind the second and third vents. For the mixed solution of antioxidant / cyclization catalyst deactivator, a solution was used in which 50 parts by weight of antioxidant (manufactured by Ciba Specialty Chemicals, Irganox 1010) and 35 parts by weight of zinc octylate (manufactured by Nippon Kagaku Sangyo, Nikka Octyx Zinc 3.6% by weight) were dissolved in 200 parts by weight of toluene. In addition, during devolatilization, pellets of styrene-acrylonitrile copolymer (AS resin: styrene unit / acrylonitrile unit ratio 73% by weight / 27% by weight, weight average molecular weight 220,000) were fed from the side feeder at a feeding rate of 15 kg / hour.
[0146] After the devolatilization was completed, the resin in a molten state remaining in the extruder was discharged from the tip of the extruder while being filtered through a polymer filter, and pelletized with a pelletizer to obtain transparent pellets (1A) of an acrylic resin containing a (meth)acrylic polymer having a lactone ring structure in the main chain as the main component (content 75% by weight) and a styrene-acrylonitrile copolymer at a content of 25% by weight. The Tg of the acrylic resin constituting the pellets (1A) was 122°C and the weight average molecular weight was 151,000.
[0147] Next, the prepared pellets (1A) were melt-extruded at 280°C using a single-screw extruder (φ=20.0 mm, L / D=25) and a coat hanger type T-die (width 150 mm) to form an acrylic resin film having a thickness of 100 μm. During the melt-extrusion, the resin film was discharged from the T-die onto a cooling roll maintained at 110°C.
[0148] Next, the produced acrylic resin film was uniaxially stretched at its free end in the MD direction (machine direction, extrusion direction) at a stretching ratio of 2.0 and a stretching temperature of 140°C using a biaxial stretching machine (TOYO SEIKI MFG. CO., LTD., TYPE EX4) to obtain a stretched acrylic resin film (F1).
[0149] (Production Example 2) In a stainless steel polymerization tank with an internal volume of 100 L equipped with a liquid lowering tank and a stirrer, 42.5 parts by weight of MMA, 5 parts by weight of N-phenylmaleimide (PMI), 0.5 parts by weight of styrene (St), 50 parts by weight of toluene as a polymerization solvent, 0.2 parts by weight of acetic anhydride as an organic acid, and 0.06 parts by weight of n-dodecyl mercaptan as a chain transfer agent were charged, and nitrogen gas was bubbled for 10 minutes while stirring at a rotation speed of 100 rpm. Next, the temperature in the tank was raised while maintaining a nitrogen atmosphere, and when the temperature in the tank reached 100 ° C, 0.075 parts by weight of t-butylperoxyisopropyl carbonate was added, and at the same time, nitrogen bubbling was started in the liquid lowering tank. Next, a mixture of 2 parts by weight of styrene and 0.075 parts by weight of t-butylperoxyisopropyl carbonate was added to the tank at a constant rate over 5 hours, while the polymerization reaction was allowed to proceed for 15 hours under reflux at a polymerization temperature of 105 to 110 ° C.
[0150] Next, 0.1 parts by weight and 0.02 parts by weight of 9,10-dihydro-9-oxa-10-phosphanenanthrene-10-oxide (HCA, manufactured by Sanko Co., Ltd.) as a phosphoric acid-based antioxidant and pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (AO-60, manufactured by Asahi Denka Co., Ltd.) as a phenol-based antioxidant were added to the obtained polymerization solution.
[0151] Next, the polymerization solution to which the antioxidant was added was introduced into a vent-type screw twin-screw extruder (Φ=29.75 mm, L / D=30) with a barrel temperature of 240°C, a rotation speed of 100 rpm, a vacuum degree of 13.3 to 400 hPa (10 to 300 mmHg), one rear vent, and four fore vents at a processing rate of 2.0 kg / hour (resin amount conversion). Next, the resin in a thermally molten state in the extruder was discharged from the tip of the extruder and pelletized by a pelletizer to obtain transparent pellets (2A) of an acrylic resin consisting of a (meth)acrylic polymer having an N-substituted maleimide structure in the main chain. The Tg of the acrylic resin constituting the pellets (2A) was 138°C and the weight average molecular weight was 200,000.
[0152] Next, the prepared pellets (2A) were melt-extruded at 280°C using a single-screw extruder (φ=20.0 mm, L / D=25) and a coat hanger type T-die (width 150 mm) to form an acrylic resin film with a thickness of 100 μm. During melt-extrusion, the acrylic resin film was discharged from the T-die onto a cooling roll maintained at 110°C.
[0153] Next, the produced acrylic resin film was uniaxially stretched at its free end in the MD direction (machine direction, extrusion direction) at a stretch ratio of 2.0 and a stretching temperature of 155°C using a biaxial stretching machine (TOYO SEIKI MFG. CO., LTD., TYPE EX4) to obtain a stretched acrylic resin film (F2).
[0154] (Production Example 3) An acrylic resin (KAMAX T-240, manufactured by Rohm and Haas) (referred to as 3A) mainly composed of a (meth)acrylic polymer having a glutarimide structure in the main chain was melt-extruded at 280°C using a single-screw extruder (φ=20mm, L / D=25) and a coat hanger type T-die (width 150mm) to form an acrylic resin film having a thickness of 100μm. During melt-extrusion, the resin film was discharged from the T-die onto a cooling roll maintained at 110°C.
[0155] Next, the produced acrylic resin film was uniaxially stretched at its free end in the MD direction (machine direction, extrusion direction) at a stretching ratio of 2.0 and a stretching temperature of 140°C using a biaxial stretching machine (TOYO SEIKI MFG. CO., LTD., TYPE EX4) to obtain a stretched acrylic resin film (F3).
[0156] (Production Example 4) A stretched acrylic resin film (F4) was obtained in the same manner as in Production Example 3, except that an acrylic resin (manufactured by Sumitomo Chemical, Sumipex B-TR) mainly composed of a (meth)acrylic polymer having a glutaric anhydride structure in the main chain was used instead of KAMAX T-240.
[0157] (Production Example 5) A stretched acrylic resin film (F5) was obtained in the same manner as in Production Example 3, except that an acrylic resin (Delpet 980N, manufactured by Asahi Kasei Chemicals) mainly composed of a (meth)acrylic polymer having a maleic anhydride structure in the main chain was used instead of KAMAX T-240.
[0158] (Production Example 6) A reaction mixture consisting of 70 parts by weight of deionized water, 0.5 parts by weight of sodium pyrophosphate, 0.2 parts by weight of potassium oleate, 0.005 parts by weight of ferrous sulfate, 0.2 parts by weight of dextrose, 0.1 parts by weight of p-menthane hydroperoxide, and 28 parts by weight of 1,3-butadiene was charged into a pressure-resistant reaction vessel equipped with a stirrer, and the reaction mixture was heated to 65°C to allow the polymerization reaction to proceed. After 2 hours had elapsed from the start of polymerization, 0.2 parts by weight of p-hydroperoxide was further added to the mixture, and 72 parts by weight of 1,3-butadiene, 1.33 parts by weight of potassium oleate, and 75 parts by weight of deionized water were continuously dropped over 2 hours. The polymerization reaction was then continued, and a latex of butadiene-based rubber polymer having an average particle size of 0.240 μm was obtained by polymerization for 21 hours from the start of polymerization.
[0159] Next, 120 parts by weight of deionized water, 50 parts by weight (solid content) of the butadiene-based rubber polymer latex prepared above, 1.5 parts by weight of potassium oleate, and 0.6 parts by weight of sodium formaldehyde sulfoxylate (SFS) were put into a polymerization vessel equipped with a cooler and a stirrer, and the inside of the vessel was fully replaced with nitrogen gas. Next, the temperature inside the vessel was raised to 70°C, and then a mixed monomer solution consisting of 36.5 parts by weight of styrene and 13.5 parts by weight of acrylonitrile, and a polymerization initiator solution consisting of 0.27 parts by weight of cumene hydroxyperoxide and 20 parts by weight of deionized water were continuously dropped into the vessel separately over a period of 2 hours to allow the polymerization reaction to proceed. After the dropping was completed, the temperature inside the vessel was raised to 80°C, and the polymerization reaction was continued for another 2 hours. Next, the temperature inside the vessel was lowered to 40°C, and the contents were passed through a 300-mesh wire net to obtain an emulsion polymerization liquid of elastic organic fine particles.
[0160] The obtained emulsion polymerization liquid of elastic organic fine particles was salted out and coagulated using calcium chloride, and the coagulated material was washed with water and dried to obtain powdered elastic organic fine particles (G1: average particle size 0.260 μm, refractive index of soft polymer layer 1.516).
[0161] Next, an acrylic resin (Asahi Kasei Chemicals, Delpet 980N) mainly composed of a (meth)acrylic polymer having a maleic anhydride structure in the main chain and the elastic organic fine particles (G1) prepared above were kneaded using a twin-screw extruder so that the acrylic resin / elastic organic fine particles was 90 / 10 (weight ratio) to prepare pellets (3A). Next, the prepared pellets (3A) were melt-extruded at 280°C using a single-screw extruder (φ=20.0 mm, L / D=25) and a coat hanger type T-die (width 150 mm) to form an acrylic resin film with a thickness of 100 μm. During melt extrusion, the resin film was discharged from the T-die onto a cooling roll maintained at 110°C.
[0162] Next, the produced acrylic resin film was uniaxially stretched at its free end in the MD direction (machine direction, extrusion direction) at a stretch ratio of 2.0 and a stretching temperature of 140°C using a biaxial stretching machine (TOYO SEIKI MFG. CO., LTD., TYPE EX4) to obtain a stretched acrylic resin film (F6).
[0163] (Production Example 7) A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen inlet tube was charged with 229.6 parts by weight of methyl methacrylate (MMA), 33 parts by weight of methyl 2-(hydroxymethyl)acrylate (MHMA), 0.138 parts by weight of an antioxidant (ADEKA CORPORATION's "ADEKA STAB (registered trademark) 2112"), 248.6 parts by weight of toluene as a non-polymerizable organic solvent, and 0.1925 parts by weight of n-dodecyl mercaptan, and the mixture was heated to 105°C while nitrogen was passed through. When refluxing began with the temperature increase, 0.2838 parts by weight of t-amyl peroxy isononanoate ("Luperox (registered trademark) 570" manufactured by Arkema Yoshitomi Co., Ltd.) was added as a polymerization initiator, and 0.5646 parts by weight of the above t-amyl peroxy isononanoate and 12.375 parts by weight of styrene (St) were added dropwise over 2 hours to allow solution polymerization to proceed under reflux at about 105 to 110°C, and after completion of the dropwise addition, the mixture was aged for a further 4 hours at the same temperature.
[0164] Next, 0.206 parts by weight of stearyl phosphate ("Phoslex A-18" manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained polymerization solution as a catalyst for the cyclization condensation reaction (cyclization catalyst), and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed under reflux at approximately 90 to 110°C for 2 hours. Next, the obtained polymerization solution was passed through a multi-tube heat exchanger heated to 240°C to complete the cyclization condensation reaction, and then introduced into a vent-type screw twin-screw extruder (L / D=52) having a barrel temperature of 250°C, one rear vent, four fore vents (referred to as the first, second, third, and fourth vents from the upstream side), and a side feeder between the third and fourth vents, and having a leaf disk-type polymer filter (filtration accuracy: 5 μm) at the tip, at a processing speed of 31.2 parts / hour (resin amount conversion), and the degree of vacuum at each vent was set to 798 hPa for the rear vent, 266 hPa for the first vent, and 27 hPa for each of the second vent to the fourth vent, to perform devolatilization. At that time, ion-exchanged water was added from behind the second and fourth vents at a rate of 0.47 parts / hour, and a toluene solution of zinc octylate (Nikka Octix Zinc 18% manufactured by Nippon Chemical Industry Co., Ltd.), 50 parts by weight of Irganox 1010 (manufactured by Chiba Specialty Chemicals), and Adeka STAB AO-412S (manufactured by ADEKA) was injected so that the mass ratio of zinc octylate was 160 ppm, Irganox 1010 was 50 ppm, and Adeka STAB AO-412S was 50 ppm relative to the obtained thermoplastic resin composition.
[0165] After the devolatilization was completed, the resin composition in a molten state remaining in the extruder was discharged from the tip of the extruder while being filtered through the polymer filter, passed through a die, and then filtered through a filter with a pore size of 1 μm (product name: Micropore Filter 1EU, manufactured by Organo Corporation). The strands were cooled in a water tank filled with cooling water maintained at a temperature within the range of 30±10°C, and then introduced into a cutter (pelletizer) to obtain pellets made of a resin composition (7A) containing a lactone ring polymer having a lactone ring structure in the main chain. The weight average molecular weight of the obtained resin composition (7A) was 132,000, the number average molecular weight was 59,000, the glass transition temperature was 121°C, the thermal decomposition onset temperature was 335°C, and the refractive index was 1.501.
[0166] Next, the produced pellets (7A) were formed into a film in the same manner as in Production Example 1 to obtain a stretched acrylic resin film (F7).
[0167] (Production Example 11) Into the stirred pure water, 0.09% by weight of an emulsion containing amorphous silica fine particles (manufactured by Nippon Shokubai, Sea Hoster KE-W30, average particle size (primary particle size) 0.28 μm, particle size distribution 1.1, solid content 20% by weight), 20% by weight of a urethane resin (manufactured by Daiichi Kogyo Seiyaku, Superflex 210, solid content 35% by weight), and 0.0007% by weight of a polyamine (manufactured by Nippon Shokubai, Epomin SP-006) were added in order and mixed thoroughly, and the mixture was passed through a 1 μm filter to obtain an easily adhesive composition (1B) which is an emulsion-like dispersion. The remainder of the easily adhesive composition after removing the urethane resin, silica fine particles, and polyamine is pure water.
[0168] (Examples 12 to 83) Using the raw materials shown in Tables 1A, 1B, and 1C below, easily adhesive compositions (2B to 73B) that were emulsion-like dispersions were obtained in the same manner as in Production Example 11. The crosslinking agent was added after the urethane resin and before the addition of the polyamine.
[0169] [Table 1A]
[0170] [Table 1B]
[0171] [Table 1C]
[0172] SF210: Superflex 210, manufactured by Daiichi Kogyo Seiyaku, solid content 35% by weight W-5030: Mitsui Chemicals polyurethane, Takelac W-5030, solid content 30% by weight CP-7020: DIC, Hydran CP-7020, solid content 40% by weight SF620: Superflex 620, Daiichi Kogyo Seiyaku, solid content 30% by weight AP-40N: DIC, Hydran AP-40N, solid content 35% by weight KE-W30: Nippon Shokubai, Seahoster KE-W30, average particle size (primary particle size) 0.28 μm, particle size distribution 1.1, solid content 20% by weight ·KE-W10: Nippon Shokubai, Seahoster KE-W10, average particle size (primary particle size) 0.11μm, particle size distribution 1.1, solid content 15% by weight SP-006: Epomin SP-006, made by Nippon Shokubai WS-700: Nippon Shokubai, Epocross WS-700, solids content 25% by weight
[0173] (3) Examples Example 1 The adhesive composition (1B) prepared in Production Example 11 was applied to one surface of the acrylic resin film (F1) prepared in Production Example 1 so that the thickness of the coating film after drying was 270 nm, and then the whole was dried at 100°C for 2 minutes. In this way, an optical film having an adhesive layer formed on one surface was obtained. The fine particles contained in the formed adhesive layer maintained the shape in the adhesive composition (1B).
[0174] (Examples 2 to 58, Comparative Examples 1 to 16) As shown in the following Tables 2A to 2C, the combination of the acrylic resin film and the easy-adhesion composition was changed, and optical films each having an easy-adhesion layer formed on one surface were obtained in the same manner as in Example 1.
[0175] The evaluation results of the optical films produced in each of the Examples and Comparative Examples are summarized in the following Tables 2A, 2B, and 2C.
[0176] [Table 2A]
[0177] [Table 2B]
[0178] [Table 2C]
[0179] (Example 59) The adhesive composition (1B) prepared in Production Example 11 was applied to one surface of the acrylic resin film (F1) prepared in Production Example 1 using a coating tester so that the thickness of the coating film after drying was 600 nm, and then the whole was dried for 2 minutes at 100 ° C. Next, the film thus obtained was stretched in the TD direction (direction perpendicular to the MD direction in the film plane, width direction during extrusion molding) at a stretching ratio of 1.5 times and a stretching temperature of 140 ° C. using a biaxial stretching machine (manufactured by Toyo Seiki Seisakusho, TYPE EX4) to obtain an optical film composed of an acrylic resin film, which is a biaxially stretched film, in which an adhesive layer containing a urethane resin and fine particles was formed on one surface.
[0180] (Comparative Example 17) As shown in Table 3 below, the combination of the acrylic resin film and the easy-adhesion composition was changed, and an optical film having an easy-adhesion layer formed on one surface was obtained in the same manner as in Example 11.
[0181] The evaluation results of the optical films produced in each of the Examples and Comparative Examples are summarized in Table 3 below.
[0182] [Table 3]
[0183] (Example 60) The acrylic resin pellets (1A) prepared in Production Example 1 were melt-extruded at a processing speed of 200 kg / h (resin amount equivalent) and a temperature of 270°C using a single-screw extruder (φ=90.0 mm, L / D=32) equipped with a polymer filter (filtration accuracy 5 μm) and a T-die at the tip to produce a strip-shaped acrylic resin film with a thickness of 220 μm. Next, the produced acrylic resin film was continuously fed to an oven vertical stretching machine following melt extrusion, and stretched (vertical stretching) in the vertical direction of the acrylic resin film (flow direction during melt extrusion, MD direction) at a stretching temperature of 142°C and a stretching ratio of 1.5 times in the stretching machine.
[0184] Further, the adhesive composition (11B) prepared in Production Example 21 was applied to one surface of the acrylic resin film after longitudinal stretching by gravure coating so that the thickness of the coating film after drying was 1050 nm (in-line coating), and then the acrylic resin film was directly fed to a tenter transverse stretching machine and stretched in its width direction (transverse stretching) at a stretching temperature of 132 ° C. and a stretching ratio of 3.0 times. In this way, an optical film (thickness 58 μm) composed of an acrylic resin film, which is a biaxially stretched film, was obtained, in which an adhesive layer (thickness 350 nm) containing a urethane resin and fine particles was formed on one main surface.
[0185] (Examples 61 to 79, Comparative Examples 18 to 20) As shown in Table 4 below, the combination of the resin pellets and the easy-adhesion composition was changed, and an optical film having an easy-adhesion layer formed on one surface was obtained in the same manner as in Example 57.
[0186] The evaluation results of the optical films produced in each of the Examples and Comparative Examples are summarized in Table 4 below.
[0187] [Table 4]
[0188] (Example 80) The acrylic resin pellets (1A) prepared in Production Example 1 were melt-extruded at a processing speed of 200 kg / h (resin amount equivalent) and a temperature of 270°C using a single-screw extruder (φ=90.0 mm, L / D=32) equipped with a polymer filter (filtration accuracy 5 μm) and a T-die at the tip to produce a strip-shaped film with a thickness of 220 μm. Next, the film thus produced was continuously fed to an oven vertical stretching machine following the melt extrusion, and stretched (vertical stretching) in the vertical direction of the film (flow direction during melt extrusion, MD direction) at a stretching temperature of 142°C and a stretching ratio of 1.5 times in the stretching machine.
[0189] Further, continuously, one main surface of the acrylic resin film after longitudinal stretching was subjected to corona treatment, and the easy-adhesion composition (11B) prepared in Production Example 21 was applied to the treated surface by gravure coating so that the thickness of the coating film after drying was 1050 nm (in-line coating). Next, the acrylic resin film was directly fed to a tenter transverse stretching machine and stretched in its width direction (transverse stretching) at a stretching temperature of 132 ° C. and a stretching ratio of 3.0 times. In this way, an optical film (thickness 58 μm) composed of an acrylic resin film, which is a biaxially stretched film, was obtained, in which an easy-adhesion layer (thickness 350 nm) containing a urethane resin and fine particles was formed on one main surface.
[0190] (Examples 81 to 82, Comparative Example 21) As shown in Table 5 below, the combination of the resin pellets and the easy-adhesion composition was changed, and an optical film having an easy-adhesion layer formed on one main surface thereof was obtained in the same manner as in Example 13.
[0191] The evaluation results of the optical films produced in each of the Examples and Comparative Examples are summarized in Table 5 below.
[0192] [Table 5]
[0193] As shown in Tables 2A to 5, the adhesive layer contains a binder resin, a polyamine, and fine particles, and the content of the polyamine in the adhesive layer is set to 0.0090% by weight to 1.4100% by weight, so that the adhesiveness between the resin film and the adhesive layer is excellent and a uniform adhesive layer can be formed. It is presumed that the use of a polymer polyamine further improves the adhesiveness between the resin film and the adhesive layer due to the interaction between the polyamine and the base film. Furthermore, it was found that the blocking resistance is also ensured by setting the content of the polyamine to, for example, 0.0489% by mass or more. This is presumed to be because the viscosity of the adhesive composition is increased by adding a sufficient amount of polyamine, and the retention force of the fine particles is increased. It is presumed that the viscosity of the matrix part of the adhesive layer is improved by adding the polyamine, and the embedding of the fine particles in the coating liquid during drying is suppressed. Furthermore, it is presumed that the polyamine also imparts the effect of suppressing the falling off of the fine particles. In contrast, in Comparative Examples 1 to 11, 13, 15, and 17 to 20, which used easy-adhesion compositions (14B to 23B, 39B, and 57B) with a polyamine content of less than 0.0090% by weight, the adhesion was not satisfactory. In Comparative Examples 12, 14, and 16, which used easy-adhesion compositions (37B, 56B, and 73B) with a polyamine content of more than 1.4100% by weight, the uniformity of the easy-adhesion composition or easy-adhesion layer was not satisfactory. This is presumably because the viscosity of the easy-adhesion composition became too high due to the excessive addition of polyamine. [Industrial Applicability]
[0194] The optical film of the present invention is used in image display devices such as LCDs, and is suitable for use in various protective films such as polarizer protective films, retardation films, and polarizing films.
Claims
1. An optical film having a resin film containing a (meth)acrylic polymer and an easy-adhesion layer formed on a surface of the resin film, The easy-adhesion layer contains a binder resin, a polyamine, and fine particles, The adhesive layer may contain a crosslinking agent, The polyamine is a polymer having a plurality of amino groups, the plurality of amino groups includes at least one selected from the group consisting of a secondary amino group and a tertiary amino group, When the easy-adhesion layer contains the crosslinking agent, the content of the polyamine is 0.0090% by weight to 1.4100% by weight in the total weight of the binder resin, the polyamine, the fine particles, and the crosslinking agent in the easy-adhesion layer; When the easy-adhesion layer does not contain the crosslinking agent, the content of the polyamine in the easy-adhesion layer is 0.0090% by weight to 1.4100% by weight in the total weight of the binder resin, the polyamine, and the fine particles.
2. The optical film according to claim 1 , wherein the binder resin comprises a urethane resin.
3. The optical film of claim 1 , wherein the plurality of amino groups includes a primary amino group, the secondary amino group, and the tertiary amino group.
4. The optical film of claim 1 , wherein the polyamine comprises a polyalkyleneimine.
5. The optical film according to claim 4 , wherein the polyalkyleneimine contains a primary amino group, the secondary amino group, and the tertiary amino group, and has a branched structure.
6. An optical member comprising the optical film according to any one of claims 1 to 5.
7. An image display device comprising the optical film according to any one of claims 1 to 5.
8. A method for producing the optical film according to any one of claims 1 to 5, comprising the steps of: A coating film of an adhesive composition containing a binder resin, a polyamine, and fine particles is formed on a surface of a resin film; The coating film is dried to form an easy-adhesion layer containing the binder resin, the polyamine, and the fine particles on a surface of the resin film; The polyamine is a polymer having a plurality of amino groups, The method for producing an optical film, wherein the plurality of amino groups include at least one selected from the group consisting of a secondary amino group and a tertiary amino group.
Citation Information
Patent Citations
Coated film
JP2003171486A
Polarizing plate and its manufacturing method, polarizing plate protective film, optical film using polarizing plate, and image display device
JP2005017704A
Adhesive composition, adhesive optical film, and image display device
JP2009035722A
Polarizer-protecting film, and polarizing plate and image display device using polarizer-protecting film
JP2010055062A
Light transmittable conductive material
JP2010153153A